Peningkatkan Kemampuan Menulis Karangan dengan Media Cerita Bergambar pada Siswa Kelas V SDN Pondok Labu 12 Pagi Jakarta Selatan 2018 - Aida Maqbulah (Sekolah Tinggi Agama Islam AL Aqidah Al Hasyimiyyah Jakarta, 2019)
This research aims to improve the learning outcomes of writing skills through pictorial story media. this research was conducted at Pondok Labu 12 Pagi Elementary School South Jakarta. Class action research using the Kemmis and MC models. taggart. the subjects of this study were 31 subjects. the steps in this study are: 1) planning; 2) implementation; 3) observation; 4) reflection. Data analysis used is qualitative and quantitative. The qualitative data uses the Miles and Hubberman models. The results of this study were pre-cycle of 55.80, the first cycle of 66.29 increased by 10.49 while in the second cycle to 85 it increased by 18.71.